Concurrent chronic lymphocytic leukemia/small lymphocytic lymphoma and hairy cell leukemia: clinical, pathologic and molecular features. Issue 13 (9th November 2020) - Obiorah, Ifeyinwa Emmanuela; Francischetti, Ivo M.B.; Wang, Hao-Wei; Ahn, Inhye E.; Wang, Weixin; Raffeld, Mark; Kreitman, Robert J.; Wiestner, Adrian; Calvo, Katherine R.
Abstract: Simultaneous occurrence of hairy cell leukemia (HCL) and chronic lymphocytic leukemia/small lymphocytic lymphoma (termed CLL) is very rare. Clinical characteristics, pathology and management of these cases have not been well described. We present six patients with CLL and HCL or HCL variant (HCL-v). Of six patients, three were initially diagnosed with CLL and later developed concurrent HCL. Two patients had concurrent HCL or HCL-v and CLL at initial diagnosis. One had HCL first, followed by concurrent CLL. Polymerase chain reaction analysis demonstrated B-cell clonality in all cases, with two distinct clonal populations in four cases, and three clonal populations in one case. Five patients were treated with a combination of a purine analog such as fludarabine, cladribine, and pentostastin with either rituximab or ibrutinib, while one received dabrefenib and trametinib. All patients achieved a durable response to either CLL or HCL-directed therapy with reduction or ablation of coexisting B-cell clones.